Pre-exposure prophylaxis persistence at two sites in an integrated primary health care programme in South Africa - Shangase, Nosipho; Jiyane, Anele; Buthelezi, Fezile; O’Connor, Cara; Brown, Ben; Rees, Kate (Frontiers in Public Health, 2025)
IntroductionHIV continues to be a public health concern and pre-exposure prophylaxis (PrEP) has become an important HIV prevention strategy. We examined PrEP persistence over time in two health facilities in Gauteng, South Africa.MethodsWe conducted a retrospective analysis of PrEP persistence between 2018 and 2022 in two government health facilities in Gauteng. Data was manually extracted from the patient medical records and captured into REDCap. We defined PrEP persistence as PrEP use over time from the date of PrEP initiation without an interruption of more than 30 days between prescription refills. We used Kaplan–Meier survival curves to illustrate time to PrEP discontinuation. We used Cox proportional hazard models to examine factors associated with PrEP discontinuation.ResultsIn total, 344 patients were included in the analysis of which 48.2% were >24 years and 68.0% were females. PrEP persistence was 65.7% at month 1, 45.9% at month 2 and 37.8% at month 3 with a median persistence time of 76 days. Individuals >24 years were less likely to discontinue PrEP (aHR = 0.55, 95%CI: 0.39–0.77) compared to those 15–19-years. PrEP discontinuation was more likely in Facility A than in Facility B (aHR = 2.96, 95%CI: 2.10–4.17).ConclusionWe have shown that most people stop taking PrEP before their second PrEP refill and individuals >24 years had longer PrEP persistence than individuals aged 15–19 years. Service delivery factors appear to have a substantial effect on PrEP persistence. Health facilities should continue to make PrEP accessible by integrating PrEP with existing services to promote PrEP persistence.